How do you solve -3/(x+1)=4/(x-1)3x+1=4x1?

1 Answer
May 2, 2017

Multiply each side by the denominators and simplify.

Explanation:

-3 / color(red)(x+1) = 4/color(blue)(x-1)3x+1=4x1

First off, multiply both sides by the denominators.

-color(blue)(3(x-1))/color(red)(x+1) = 43(x1)x+1=4

-color(blue)(3(x-1))= color(red)(4(x+1)3(x1)=4(x+1)

Then, expand the brackets.

color(blue)(-3x+3) = color(red)(4x + 4)3x+3=4x+4

Rearrange the equation.

-3x - 4x = 4 - 33x4x=43

              #x=-1/7#

Double check your answer by substituting x=-1/7x=17 back into the original equation.

-3 / color(red)(-1/7+1) = 4/color(blue)(-1/7-1)317+1=4171

color(red)(-3.5 = color(blue)(-3.5)3.5=3.5

Therefore, your answer x=-3.5x=3.5 is correct.